Application of a Local Dynamic Model of Large Eddy Simulation to a Marine Propeller Wake - Lien Young; Xing Zheng (Applied Sciences, 2023)
With recent development of computer technology, the use of large eddy simulation method to solve industrial problems is gaining acceptance. From a theoretical and applied perspective, a local dynamic k-equation subgrid-scale model is applied to study the flow over a marine propeller. This local dynamic SGS model of LES have already been used in simple flows such as classical Taylor-Green vortex flow to investigate its robustness and superior than other dynamic SGS models. In this paper it will be applied to a more complex flows, i.e., simulation of a marine propeller wake, to further evaluate its ability range. 42 intentionally selected numerical experiments were conducted. The results of this local dynamic model of LES shows some superior than the dynamic Smagorinsky model, and well captures the wake evolution mechanism of a propeller, although which actually depends on its geometry.